Exploring small and medium enterprises (SMEs) food packaging as a touch-point to promote nation branding at Kuala Lumpur International Airport (KLIA) - Tan, Si Man (2019)
The purpose of this study is to investigate the potential of national identity to be usedas a promotion factor by Malaysian Small and Medium Enterprises (SMEs), through its food packaging.The Kuala Lumpur International Airport (KLIA International Airport, KLIA) was chosen as the targetlocation because the airport has the potential to trigger impulsive buying behaviors amongcustomers. Qualitative approaches through semi-structured interviews were used as data collection.This study involves15 respondents involved, comprising ten international students, three graphic designers, and twoexperts in the field of advertising and branding. Grounded theory is used in the process ofanalyzing data by dividing data into respective categories and codes. This study identifies threeimportant categories comprising of country of origin (COO), semiotic, and combined elements (COOand semiotic). The findings show that the use of national branding in PKS food packaging is able topromote national identity and national branding effectively. This study suggests that SMEs shouldinvest in packaging as it is one of the most important elements for brand building andproductive aspects for products and countries.